Differential Experiences of Displacement in Transit through Mexico. The Ethnic Bridges among Garífuna and Honduran-Latino Groups (2024)
This article focuses on the differential experiences of migratory displacement between two ethnic groups from Honduras; the Afro-American Garifuna and Latinos. It seeks to compare the differential migration strategies of these two ethnically distinct displaced populations from the same country. Both move towards the same destination starting with transit through Mexico and then attempting to reach the United States. The manuscript is based on fieldwork conducted in migrant shelters within the irregular migratory route in Mexico, also, in New Orleans and Houston, two major destinations for the Garifuna population in the U.S. The paper consequently focuses on the case of the Garifuna, for whom it identifies the processes of territorial exclusion in which they are involved from the origin, nevertheless put the Garifuna population at an advantage over their non-Garifuna countrymen Latinos concerning the migratory process and their migration networks, specifically for having a better previous integration in the country of destination.